The Bangsamoro project the role of Malaysia, Indonesia and Brunei in the Mindanao peace process - Bajo, Ann Febel Q.; Bajo, Ann Febel Q.; Baviera, Aileen S.P. (Quezon City Asian Center, University of the Philippines Diliman, 2018)
"The study focuses on the internationalization of the Bangsamoro problem, particularly the roles of external states and their behavior in Mindanao conflict as a function of their foreign policies. The framework in understanding external involvement surmises that motives cause interventions, which produce outcomes. Motive refers to the interest behind foreign intervention. It is the driving force that causes states to intervene. Intervention strategies refer to the methods of intervention while outcome is the possible result of external state involvement.
"External states being involved and playing a critical role in resolving internal conflicts is an existing practice in international relations. There have been occasions when internationalizing domestic issues has shown positive effects on internal conflicts. One case in point is the Mindanao peace process, which is an internal issue that has an external dimension. Certain Southeast Asian states, namely, Malaysia, Indonesia and Brunei were involved in the Bangsamoro peace process.
"Malaysia had several reasons to be involved that motivated it to play multiple roles in the peace process--a peace facilitator and as peacekeepers, and these resulted in desired outcomes for the parties. The motivation behind Malaysia's participation is predominantly instrumental. The main reasons for their interventions are national interest and regional security. They have direct interest on the issue that would help them attain their national goals. As peace facilitator, Malaysia secured and sustained the peace talks until an agreement between the Philippine government and the Moro Islamic Liberation Front had been concluded. As peacekeepers, Malaysia deployed "boots on the ground" to allow them to reach out to Muslim communities and prevent armed skirmishes. Malaysia's intervention contributed to a peace agreement that benefited both Malaysia and the Philippine government.
"Indonesia played different roles in the earlier GPH-MNLF and the more recent GPH-MNLF peace processes. Its participation was more affective in nature, as opposed to instrumental, and its primary concern was security. It also emphasized cooperation through an international body as an intervention mechanism rather than employing a bilateral approach towards the Philippines. In the case of Brunei, no strong evidence surfaced to explain Brunei's participation in the peace process. It is believed that they actively participated in the international Monitoring Team in order to promote regional security.
'States, therefore, are motivated to intervene in another country's domestic conflict primarily because their interest are affected. How they define their interests influences the type of intervention, which in turn affect outcomes."--Author
Thesis
Keywords: Mindanao (Philippines) -- Economic conditions